Computer-Enhanced Visual Learning Method to Teach Endoscopic Correction of Vesicoureteral Reflux: An Invitation to Residency Training Programs to Utilize the CEVL Method - Michael Bauschard; Max Maizels; Andrew Kirsch; Martin Koyle; Tony Chaviano; Dennis Liu; Rachel Stork Stoltz; Evelyn Maizels; Michaella Prasad; Andrew Marks; David Bolnick (Advances in Urology)
Herein we describe a standardized approach to teach endoscopic injection therapy to repair vesicoureteral reflux utilizing the CEVL method, an internet-accessed platform. The content was developed through collaboration of the authors' clinical and computer expertises. This application provides personnel training, examination, and procedure skill documentation through the use of online text with narration, pictures, and video. There is also included feedback and remediation of skill performance and teaching “games.” We propose that such standardized teaching and procedure performance will ultimate in improved surgical results. The electronic nature of communication in this journal is ideal to rapidly disseminate this information and to develop a structure for collaborative research.